A Mixed Method Evaluation of a Culturally Adapted, Brief, Bullying Bystander Intervention for Middle School Students. Issue 3 (2nd September 2019) - Moran, Molly; Midgett, Aida; Doumas, Diana M.; Porchia, Sherise; Moody, Steve
Abstract : The purpose of this mixed method study was to examine the appropriateness of a brief, bullying bystander intervention (STAC) adapted for a middle school in a low-income, rural community with a predominantly White and Hispanic student body. We were also interested in understanding the experiences of the students who participated in the intervention. Quantitative analysis suggested that students gained knowledge about bullying, increased their confidence to intervene in bullying situations, and used the STAC strategies to intervene in bullying behavior. Analyzing the qualitative data using Consensual Qualitative Research methodology ([CQR] Hill et al.) revealed four domains in which students (a) reported using the STAC strategies across multiple contexts and settings, (b) spoke about fears related to intervening in bullying, yet intervened despite those fears, (c) described emotional benefits experienced after participating in the intervention and while using the STAC strategies, and (d) reported stronger interpersonal relationship after participating in the STAC intervention. This study extends the literature by providing preliminary support for a brief, bystander intervention adapted to address the need for culturally relevant bullying interventions for low-income, rural, ethnically-blended schools.